"Death Is Better Than Misery": Elders' Accounts of Abuse and Neglect in Ethiopia. (December 2015) - Chane, Samson; Adamek, Margaret E.
As the proportion of elders in developing nations increases and the ability of families to meet their needs is stretched thin, the risk of elder abuse will grow. This study examined the types and nature of abuse and neglect from the perspective of elders in Ethiopia who experienced abuse in noninstitutional settings. A qualitative design guided by hermeneutic phenomenology was used to explore the lived experiences of abuse and neglect of 15 Ethiopian elders. Nine women and six men ranging in age from 64 to 93 years were interviewed. Most were victims of multiple forms of abuse, especially financial exploitation, emotional abuse, and neglect. Economic vulnerability was a clear underlying factor contributing to elders' risk for encountering abuse. Effective prevention efforts must address the societal level factors that ultimately contribute to elder abuse while also holding individuals responsible for their harmful behaviors against elders.